Impact of Physician Physical Activity on Well-Being, Counseling Practices, and Performance: A Systematic Review - Stephen J. Perle; Charles A. Baumann; William B. Dyke; John R. Baumann; Alexander D. Jeffs; Elizabeth O. Moreton; Jackson Perry; Nicholas C. Bank; Douglas S. Weinberg; R. Alexander Creighton (Health Education & Behavior, 2026)
Physicians are routinely exposed to high levels of occupational stress and demanding cognitive load. Although physicians often report higher levels of physical activity than the general population, physical activity behaviors are variable, and some physicians still do not meet recommended activity guidelines. This systematic review examined whether physician physical activity impacts several professional domains: well-being and burnout, patient counseling and role-modeling behaviors, and cognitive function or clinical performance. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, PubMed, Scopus, and SportDiscus were searched in October 2025. Twenty-three studies met the inclusion criteria. Across 10 studies evaluating physician well-being, higher physical activity was consistently associated with lower burnout, reduced stress, fewer symptoms of depression and anxiety, greater professional fulfillment and personal accomplishment, and higher quality of life. Twelve studies demonstrated associations between physicians’ physical activity and greater frequency, confidence, and perceived effectiveness of physical activity counseling, with estimates ranging from odds ratio (OR) 2.43 to 5.72 among studies reporting ORs. Patients also reported greater trust in physically active physicians. Evidence directly linking physician physical activity to objective clinical performance outcomes was limited. One multimodal wellness intervention study incorporating physical activity reported improvements in self-reported cognitive adaptability. However, the independent effect of physical activity could not be isolated. Overall, physician physical activity appears associated with improved well-being and increased patient counseling, suggesting a promising target for clinician wellness initiatives.